On multipath balancing and expanding for wireless multimedia sensor networks. (24th February 2012) - Chen, Min; Leung, Victor C.M.; Shu, Lei; Chao, Han–Chieh
Multiple disjointed paths have been demonstrated to be effective in delivering multimedia traffic in Wireless Sensor Networks (WSNs), and improving the network performance in terms of bandwidth aggregation, reliability and network lifetime. In this paper, we investigate the use of Directional Geographical Routing (DGR) for multipath construction for multimedia data dissemination, and identify the challenging issue of achieving multipath balancing in proximity to the source/sink. The path construction is divided into expanding phase, parallel phase and converging phase in the proposed scheme, which includes two key algorithms, i.e., the detection algorithm for path construction phase and the deviation angle adjustment algorithm. Simulation results verify the effectiveness of the proposed scheme.